A interação entre o professor e o intérprete de libras na sala de aula e a inclusão de alunos surdos - SIQUEIRA, Adrielly de Oliveira (2023)
This work deals with school inclusion, questioning the pedagogical relationship between teachers and the Libras interpreter in the process of inclusion of deaf students. The general objective is to reflect on the pedagogical relationship in the inclusive classroom. The theoretical framework included Quadros (2008), Gebarae Barros (2014), Lacerda (2020), Melo (2013) and others. The research is part of a qualitative approach and was developed through a case study. Fieldwork took place at the M.E.F. Dr. Anthodio Barbosa in the city of Tomé-Açu, with a group of teachers and a Libras interpreter as participants. In data collection, we used observation and the application of questionnaires. As a result, the relationship between teachers and Libras interpreters is still very timid, which affects the process of inclusion of deaf students; despite the numerous changes in inclusive education, we perceive weaknesses in this service, especially regarding inclusive teacher training.